Os diferentes usos do “AGORA” no português brasileiro contemporâneo: uma proposta didática a partir dos gêneros meme e anedota - Santarém, Aline Tozzi Vieira (2020)
Currently, we can observe the teaching normative grammar practice be used by the teachers creating a gap between the Portuguese language in use and the mother/first language teaching. In this context, this research aims to the teaching of the different uses of “now” to the final-grade students at a public state elementary school supported, mainly, by Educational Sociolinguistics and Linguistic Variation Pedagogy (BORTONI-RICARDO, 2001, 2004, 2014; BAGNO, 2012, 2015, 2016; FARACO, 2008, 2017; ZILLES, 2016; CYRANKA, 2007, 2014, 2015). Besides, the current research will be guided by some functionalists principles resorting to the Grammaticalization theory (TRAUGOTT, 1991; HEINE, 1991; GONÇALVES, 2007; VIEIRA, 2013) and scientific researches related to the uses of “now” in Contemporary Brazilian Portuguese (LINS, SILVA, 2012; GRYNER, 2007) in the light of functionalist theory. This because the main purpose of this research is the creation of a didactic proposal regarding the Educational Sociolinguistics that contemplates the teaching of “now” and apply such proposal to the to the final-grade elementary students. From the functionalist contributions to the Portuguese language teaching (NEVES, 2000, 2003, 2009), we intend to approach the different uses of “now” in written texts in Contemporary Brazilian Portuguese, therefore, not even “now” as a time adverb, as it is (invariably) described according to the normative grammar textbooks. Through the approach will support this scientific study, “now” will be taught as an item, for example, that resumes a speaking expression or even appears as an adversative connective. It is worth mentioning, the variations of the use of “now” will be observed in several situations of use, in spotlight for the use in written texts, observing such memes and jokes. The choice for these kinds of genres justifies due to these genres present less linguistic variation monitoring, therefore they become sources of susceptible linguistics variation. The analyses of the item “now” in these genres were productive in many different ways of use beyond the adverb classification. Therefore, through the studies of the different uses of “now” in memes and jokes, in the didactic proposal which is presented to the students in the final grade in this research, we’re going to have the opportunity through the reflection of the language in use, focusing on the different uses of “now”, discuss concretely and significantly about the heterogeneity of language, as well as, the variation phenomenon and linguistics changes. Keywords: Educacional Sociolinguistics. Linguistic Variation Pedagogy. Portuguese Language Teaching. Gramaticalization. Linguistic Analysis.